2021
DOI: 10.1088/1757-899x/1074/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble Deep Learning for Brazil Currency Coin Prediction

Abstract: In this present fast growing environment the automatic coin reorganization and identification machines has a vital role in all financial allied fields. At present most of coin recognition techniques are depends on physical properties of the coin like length, width, weight etc. Whereas image processing techniques are based on extraction of colour of the coin, edge features of the coin and shape of the coin. For recognition and detection of Brazil currency we have designed Machine Learning, Deep Learning (DL) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…From this classification results data, it is concluded that the newly proposed technique is giving better performance results than the technique used in Ref. [36,37,38,39]. This is because most of the existing techniques used traditional machine learning algorithms which highly feature dependents.…”
Section: G Comparative Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…From this classification results data, it is concluded that the newly proposed technique is giving better performance results than the technique used in Ref. [36,37,38,39]. This is because most of the existing techniques used traditional machine learning algorithms which highly feature dependents.…”
Section: G Comparative Analysismentioning
confidence: 88%
“…In the case of Brazil, a country renowned for its rich cultural history and diverse coinage, the task of classifying Brazilian coins presents unique challenges due to the substantial variations in size, design, and appearance across different denominations and minting years. Currency recognition techniques may be used in coinbased printing devices, vending machines, automated toll gates, various bank hardware, etc., [1]. According to the prediction made by the International Chamber of Commerce (ICC), there will be a global financial loss of US $2.3 trillion by 2022 due to the exchange of fake currencies [2].…”
Section: Introductionmentioning
confidence: 99%
“…This paper is oriented around Indian currency. The authors followed the same structure as Rahman et al [2], wherein they created a dataset that contains both Indian banknotes as well as coins of different denominations and three state of the art deep learning frameworks, namely Alexnet, Googlenet, and Vgg16, were trained, tuned and compared. The result showed that Googlenet (with 22 convolution layers) was the least accurate with an accuracy of 88%, while Vgg16 (with 16 convolution layers) was the most accurate.…”
Section: Ranjendra P and Anithaashri Tp (2020) [8]mentioning
confidence: 99%
“…Such systems are deployed to reduce the odds of human error and fast-track the repetitive process of counting and sorting a large number of coins. While traditionally, such systems make use of the mechanical and electromagnetic properties [2] of the coins to classify them, it is due to the enormous development in the field of computer vision and artificial intelligence that new systems are coming forth that utilizes robust neural networks to detect, segment and classify coins based on the images of the coins processed in real-time. Although the majority of the application stems from the sectors mentioned above yet due to the increasing reliability of coin classification systems and the increasing availability of computational resources for the average person, various studies have been done aiming to develop a system that can assist visually impaired people in identifying and classifying real currency [ [3], [4]].…”
Section: Introductionmentioning
confidence: 99%